Analysis of Influencing Factors Performance Member of the People's Representative Council - Sutiyem Sutiyem; Dessy Trismiyanti; Suhery Suhery; Yulina Eliza (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This research is to test the influence of competence, communication, and commitment on employee performance.Secretariat of the DPRD of West Sumatra Province. Determination of the sample using purposive sampling with a sample size of 93 people. Data collection was carried out by distributing questionnaires and analyzed using SPSS version 24.Findings– Based on the results of the study, it shows that partially each variable of Competence, Communication, and Commitment has a positive and significant effect on performance. Based on the results of the simultaneous test, it explains that Competence, Communication, and Commitment together have a significant effect on performance.For Competence,It is recommended that agencies include employees in technical guidance, training (diklat), socialization, employee education according to their field of duty or main tasks and functions to improve employee knowledge.For Communication, it is recommended that agencies be moreimprove communication between leaders and subordinates and between subordinates and superiors in order to create good work enthusiasm and employee work performance